2006
DOI: 10.1111/j.1533-2500.2006.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

An Opioid Screening Instrument: Long‐Term Evaluation of the Utility of the Pain Medication Questionnaire

Abstract: Abstract:The Pain Medication Questionnaire (PMQ) was designed to assess the risk for opioid medication misuse in chronic pain patients. A preliminary study showed a positive relationship between higher PMQ scores and concurrent measures of substance abuse, psychopathology, and physical/ life-functioning. Using a larger sample size, the present study sought to replicate these findings, and to expand upon them by examining the relationship between PMQ scores and various treatment outcomes. The PMQ was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 19 publications
7
52
0
Order By: Relevance
“…High risk patients were also found to be less active in managing their pain condition, and to have a greater propensity to produce pessimistic and catastrophic thoughts about their pain symptoms. The association that emerged, between high PMQ scores and the presence of symptoms of depression, appears to be in line with the findings of Holmes et al (2006) in their work assessing the long-term utility of the PMQ in 271 subjects. In this study the low risk patients had mean BDI scores that were significantly lower than those of the high risk of misuse group.…”
Section: Discussionsupporting
confidence: 73%
“…High risk patients were also found to be less active in managing their pain condition, and to have a greater propensity to produce pessimistic and catastrophic thoughts about their pain symptoms. The association that emerged, between high PMQ scores and the presence of symptoms of depression, appears to be in line with the findings of Holmes et al (2006) in their work assessing the long-term utility of the PMQ in 271 subjects. In this study the low risk patients had mean BDI scores that were significantly lower than those of the high risk of misuse group.…”
Section: Discussionsupporting
confidence: 73%
“…Subsequently, in a replication of this initial aforementioned study, Holmes and colleagues revealed some additional important characteristics that were associated with patients with high PMQ score [24]. These characteristics included the following: the request for early refills for prescription medications was 3.2-times more than in patients with low PMQ score; the history of substance abuse problems were 2.6-times greater than in patients with low PMQ score; the dropout rate from an interdisciplinary pain management program was 2.3-times greater than in patients with low PMQ score; and, overall, there was a diminished biopsychosocial functioning level relative to patients with low PMQ score.…”
Section: Variability In Screening Prior To Initiating Opioid Therapymentioning
confidence: 82%
“…Gatchel and colleagues initially developed the PMQ in order to assess the risk of medication misuse in chronic pain patients in a series of four studies [24,25,29,30]. In the initial study of this series, Adams et al reported that there was a positive relationship between high PMQ scores (high scores = higher potential risk) and concurrent measures of substance abuse, psycho pathology and physical-life functioning [29].…”
Section: Variability In Screening Prior To Initiating Opioid Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of assessment tests have been developed for this purpose during recent years [6,9]. For example, the Pain Medication Questionnaire (PMQ) has received a great deal of interest as a result of initial studies by Gatchel and colleagues [12][13][14][15]. The PMQ was initially designed to assess the risk of medication issues in chronic pain patients, and Adams and coworkers found that there was a positive relationship between higher PMQ scores and concurrent measures of substance abuse, psychopathology and physical/life functioning [12].…”
Section: Editorial Gatchelmentioning
confidence: 99%